Mitochondrial disorders in children: toward development of small‐molecule treatment strategies - Werner JH Koopman; Julien Beyrath; Cheuk‐Wing Fung; Saskia Koene; Richard J Rodenburg; Peter HGM Willems; Jan AM Smeitink (EMBO Molecular Medicine)
Abstract This review presents our current understanding of the pathophysiology and potential treatment strategies with respect to mitochondrial disease in children. We focus on pathologies due to mutations in nuclear DNA‐encoded structural and assembly factors of the mitochondrial oxidative phosphorylation (OXPHOS) system, with a particular emphasis on isolated mitochondrial complex I deficiency. Following a brief introduction into mitochondrial disease and OXPHOS function, an overview is provided of the diagnostic process in children with mitochondrial disorders. This includes the impact of whole‐exome sequencing and relevance of cellular complementation studies. Next, we briefly present how OXPHOS mutations can affect cellular parameters, primarily based on studies in patient‐derived fibroblasts, and how this information can be used for the rational design of small‐molecule treatment strategies. Finally, we discuss clinical trial design and provide an overview of small molecules that are currently being developed for treatment of mitochondrial disease.